Spleen rupture during labor - Bessow, Camila Karsburg; Müller, Ana Lúcia Letti; Balbinotto, Rosi Pereira; Lubianca, Jaqueline Neves (Clinical and Biomedical Research, 2016)
Background: A ruptured splenic artery aneurysm is rare but potentially fatal and has a greater chance of occurring during pregnancy. Case: A 38-year-old pregnant woman was admitted to hospital in labor and presented with dyspnea and hypovolemic shock during the expulsion stage. After delivery, a bedside ultrasound was performed and showed a large amount of free fluid in the abdominal cavity. The patient was submitted to an exploratory laparotomy, which found a ruptured splenic hilum, and anatomopathological examination confirmed a ruptured splenic artery aneurysm. Both mother and baby survived without sequelae. Conclusion: Ruptured aneurysm must be considered among the causes of hypovolemic shock in pregnancy, and early detection can reduce the morbidity and mortality of this event.